Strengthening Child-Friendly Volunteer through Training of Trainers: An Adult Education Approach - Suharta, Robertus Belarminus; Kusumawardani, Erma; Sugito, Sugito; Septiarti, Serafin Wisni; Setiana, Dafid Slamet (FKIP Universitas Lampung, 2024)
Abstract: Strengthening Child-Friendly Volunteer through Training of Trainers: An Adult Education Approach. Objective: Strengthening human resources is an effort carried out with the aim of regenerating and continuity of resources so that they can be utilized optimally in the future. Method: This research using participatory action research method using an adult education approach. Implementation of research consists of the following process stages, namely: making preparations, carrying out training activities, carrying out evaluations, and follow-up development. Finding: The village officials which is focused on helping the village to continue to be consistent in carrying out activities for the community. FGD analysis of the needs of the target group which is a follow-up to socialization activities. Preparation of child-friendly village development carried out by researchers through the delivery of material as well as discussion activities guided to analyze the response of child-friendly village managers in identifying problems and obstacles still being faced as well as actions taken in the context of developing child-friendly villages. Conclusion: The village government is encouraged to support child-friendly village managers in carrying out activities such as preparing open land to facilitate child-friendly activities. Keywords: adult learning, child-friendly, volunteer, training for trainer. DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202444